Eat, pray, love one woman's search for everything - Gilbert, Elizabeth (London Bloomsbury, 2011)
It's 3 a.m. and Elizabeth Gilbert is sobbing on the bathroom floor. She's in her thirties, she has a husband, a house, they're trying for a baby - and she doesn't want any of it. A bitter divorce and a turbulent love affair later, she emerges battered and bewildered and realises it is time to pursue her own journey in search of three things she has been missing: pleasure, devotion and balance. So, she travels to Read more
2
Keywords: English stories